2017
DOI: 10.1590/s1679-87592017131506503
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the beach silverside Atherinella blackburni (Atherinopsidae) in a tropical sandy beach, Southeastern Brazil

Abstract: Gonzalez and Vaske Junior: Feeding of Atherinella blackburni in Brazil 346Feeding ecology of the beach silverside Atherinella blackburni (Atherinopsidae) in a tropical sandy beach, Southeastern Brazil A ecologia alimentar do peixe-rei (Atherinella blackburni) na zona de arrebentação de uma praia arenosa tropical, localizada no sudeste do Brasil, foi acessada a partir da análise do conteúdo alimentar de 198 peixes. Fatores como o tamanho, a estação do ano e o período do dia foram analisados para compreender com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In this study only A. blackburni was subject to reproductive cycles, so it was the only species in which this variable could influence K. But, similarly to the other species in this study, mainly juvenile individuals without reproductive cycle influence, A. blackburni showed no variation of K value between seasons. Atherinella blackburni is found only on the shores of the Atlantic Ocean, always occurring in the surf zone (Schultz, 1949;Gilbert and Caldwell, 1967;Gonzales and Vaske-Júnior, 2017). This is the only species among others in our study that presents a complete life cycle in this environment.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study only A. blackburni was subject to reproductive cycles, so it was the only species in which this variable could influence K. But, similarly to the other species in this study, mainly juvenile individuals without reproductive cycle influence, A. blackburni showed no variation of K value between seasons. Atherinella blackburni is found only on the shores of the Atlantic Ocean, always occurring in the surf zone (Schultz, 1949;Gilbert and Caldwell, 1967;Gonzales and Vaske-Júnior, 2017). This is the only species among others in our study that presents a complete life cycle in this environment.…”
Section: Discussionmentioning
confidence: 54%
“…We might suggest that temperature does not affect abundance or K in A. blackburni on Praia Grande beach. Gonzales and Vaske-Júnior (2017) showed that the availability of food in the surf zone varies according to physicochemical conditions and season, but despite that, they confirm that A. blackbuni has a generalist strategy and feeds on any available organisms along the year. Considering the relative low temperature variation (betewn 18 oC and 22oC, see: Roling et al, 2007), the constantly available food at the study area (Lasiak, 1981;Carter, 1988;Brown and Mclachlan, 1990), and based on stable allometric condition factor we might suggest A. blackburni does not have a well-defined reproductive seasonality in the Brazilian southeastern coast.…”
Section: Discussionmentioning
confidence: 93%